2022
DOI: 10.3390/healthcare10122378
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Edentulism in a Sample of Mexican Adults with and without Type 2 Diabetes

Abstract: The objective of the present study was to compare the prevalence of edentulism in Mexican adults with and without a diagnosis of type 2 diabetes mellitus (T2DM) when they are seeking dental care. A cross-sectional study was conducted on 1921 medical records of Mexican adults 40 years of age and older who sought dental care at clinics of a public university in Mexico. The dependent variable was edentulism, clinically determined through an oral examination. The main independent variable was the self-report of pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 49 publications
0
3
0
1
Order By: Relevance
“…The reference lists from the selected studies were hand-searched, but no additional papers were identified as suitable. Therefore, seven papers [26][27][28][29][30][31][32] were selected and processed…”
Section: Search and Selection Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The reference lists from the selected studies were hand-searched, but no additional papers were identified as suitable. Therefore, seven papers [26][27][28][29][30][31][32] were selected and processed…”
Section: Search and Selection Resultsmentioning
confidence: 99%
“…The reference lists from the selected studies were hand‐searched, but no additional papers were identified as suitable. Therefore, seven papers 26–32 were selected and processed for further data extraction. A schematic overview of the search and selection process is presented in the flow chart in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…La importancia clínica de este microorganismo, de la enfermedad periodontal y sus consecuencias, se debe a la relación que guarda con diferentes enfermedades sistémicas, con quienes además comparten factores de riesgo biológicos, conductuales y psicosociales comunes (11), entre ellas la diabetes, las enfermedades cardiovasculares, el síndrome del ovario poliquístico, cáncer de pulmón, enfermedad renal crónica, Alzheimer, deterioro cognitivo relacionado con la edad, artritis reumatoide, obesidad, entre otras (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23).…”
Section: Introductionunclassified
“…According to a national survey in Mexico, approximately 10% of adults noninstitutionalized between 45 and 54 years old, 25% between 65 and 74 years old, and 30% between 65 and older are edentulous [ 12 ]. In a recent study, overall edentulism prevalence observed was 8.4% [ 13 ]. Regarding tooth loss, previous studies have observed the following results (mean age = 41.6 years): 52.7% had at least 1 tooth loss, with a mean of 2.9 tooth loss [ 14 ].…”
Section: Introductionmentioning
confidence: 99%